To what extent do law firms in the Middle East strengthen access to justice? - Bleskine, Cecile (2015)
As corporate social responsibility (‘CSR’) gains greater emphasis in the values and identity of organisations, pro bono work – a long standing practice rooted in the English and American legal professions to make access to justice available to all – has in turn become an integral component of the CSR agendas and programs of law firms. This dissertation investigates the extent to which law firms strengthen access to justice for people in need through the provision of pro bono work in the Middle East region. Whilst there is ample literature on legal pro bono work undertaken in other parts of the world – mainly the United States and the United Kingdom – there is a gap in the literature when it comes to pro bono work in the Middle East. Such a study is therefore important in identifying the status of pro bono work in this part of the world, as well as shortcomings and opportunities in this area.